2015
DOI: 10.4999/uhod.15739
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Efficiency of HE4 and CYFRA 21-1 in Patients with Lung Cancer.

Abstract: Lung cancer is the leading cause of cancer related deaths. Despite the modern diagnostic and therapeutic advances, 5-year survival rate of all cases of lung cancer does not exceed 15%. Therefore, sensitive tumor biomarkers are needed for the early detection and differential diagnosis of lung cancer. The aim of the study was to evaluate the diagnostic efficiency of HE4 (Human epididymis protein 4) and CYFRA 21-1 in patients with lung cancer. Serum samples were collected from 80 patients; Group 1 consisted of 53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Figure S1 is a flowchart depicting the study selecting process. Finally, 16 studies with 3,202 subjects (1,756 lung cancers and 1,446 controls) were identified (8,12,13,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) (8,19,22,(25)(26)(27) and tuberculosis (21). Only one study was industry funded (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure S1 is a flowchart depicting the study selecting process. Finally, 16 studies with 3,202 subjects (1,756 lung cancers and 1,446 controls) were identified (8,12,13,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) (8,19,22,(25)(26)(27) and tuberculosis (21). Only one study was industry funded (28).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic accuracy of human epididymis secretory protein 4 for lung cancer: a systematic review and meta-analysis Human epididymis secretory protein 4 (HE4) has been regarded as a tumor marker for ovarian cancer for a long time (9,10). Interestingly, several studies have revealed that it is also a useful diagnostic marker for lung cancer (11)(12)(13), but the results of these studies are heterogeneous. Therefore, we performed a systematic review and meta-analysis to assess the diagnostic accuracy of HE4 for lung cancer.…”
Section: Original Articlementioning
confidence: 99%
“…Accumulating evidence has demonstrated that HE4 could be used to diagnose lung cancer. [1421,23] However, to assess the value of HE4 for diagnosing lung cancer, the data of evidence-based medicine from different research centers should be subjected to pooled analysis. The impact of race, assay method, and type of lung cancer should be determined.…”
Section: Discussionmentioning
confidence: 99%